(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article discusses new approaches in education require new methods in working with information. If earlier the library and the teaching room were sufficient for the needs of the students and teachers, today there is a need to talk about the modern system of storing, processing and broadcasting of various media didactic material. Such a system to date, in our opinion, can be a virtual media library equipped with unique content created on the basis of such an authoritative institution as a museum that could set a bar of quality, providing the user with only encyclopaedically accurate information.